2006
DOI: 10.1007/s00220-006-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

A Variational Principle for KPP Front Speeds in Temporally Random Shear Flows

Abstract: We establish the variational principle of Kolmogorov-PetrovskyPiskunov (KPP) front speeds in temporally random shear flows inside an infinite cylinder, under suitable assumptions of the shear field. A key quantity in the variational principle is the almost sure Lyapunov exponent of a heat operator with random potential. The variational principle then allows us to bound and compute the front speeds. We show the linear and quadratic laws of speed enhancement as well as a resonance-like dependence of front speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…A related problem is to study Hamiltonians with unbounded temporal fluctuations. For reaction-diffusion fronts in incompressible random advection, temporal randomness is found to regularize the dominance of extreme events and promote mixing; hence the speed of propagation is asymptotically a deterministic constant [13,7,9]. It is conceivable that similar results (or homogenization) hold for HJ equations in unbounded time-dependent random media under suitable conditions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A related problem is to study Hamiltonians with unbounded temporal fluctuations. For reaction-diffusion fronts in incompressible random advection, temporal randomness is found to regularize the dominance of extreme events and promote mixing; hence the speed of propagation is asymptotically a deterministic constant [13,7,9]. It is conceivable that similar results (or homogenization) hold for HJ equations in unbounded time-dependent random media under suitable conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, existence and estimates of front speeds in unbounded temporal random flows have been studied for reaction-diffusion-advection equations [13,7,9]. It is worthwhile for a future work to study whether HJ averaging in unbounded time-random regime behaves similarly.…”
Section: Introductionmentioning
confidence: 99%
“…The two-scale discretization scheme is much more efficient than the one-scale discretization while achieving the same accuracy. In future work, we plan to study front speed ensemble in space-time random flows [29,31] by extending the two-scale method to parabolic problems.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental problem is to characterize and compute large-scale front speeds in random flows [10,19,30,31,39]. The Kolmogorov-Petrovsky-Piskunov (KPP) minimal front speeds admit a variational characterization in terms of the principal eigenvalue or principal Lyapunov exponent of an associated linear operator [6,5,16,37,28,29]. The variational principle of KPP front speeds makes accurate and efficient analytical and numerical studies possible.…”
mentioning
confidence: 99%
“…It has been shown in [4,12] that the flow u(x) is relaxation-enhancing if and only if u has no first integrals in with a non-negative nonlinearity f (s) that vanishes at s = 0 and s = 1 -such equations appear in flame propagation as well as many other applied problems. It has been shown that a flow may speed-up a flame [9,18,23,28,30] or quench the propagation [11,17,24,37,38] as A → +∞.…”
Section: Introductionmentioning
confidence: 99%